Tantangan PR dalam Mempromosikan Kawasan Bintan Resorts di Masa Pandemi Covid-19 - Nelson, David; Yoedtadi, Moehammad Gafar (Prologia, 2024)
Bintan Resorts is a mainstay tourism area for the Riau Islands which has been affected economically due to the Covid-19 pandemic. Various efforts have been made to maintain business continuity in the Bintan Resort area, one of which is by increasing promotion through the role of public relations. The purpose of this research is to find out how public relations helped advertise the Bintan Resorts area during the Covid-19 pandemic. This research approach uses descriptive qualitative to see, identify, and explain the function of public relations in promoting the Bintan Resort area during the Covid-19 pandemic. The research uses a case study or a single case, in the form of PT. Bintan Resort Cakrawala. The research subject is the public relations of PT. Bintan Resort Cakrawala, while the object of research is the role of public relations in promoting the Bintan Resort area. Data collection techniques are interviews, observation and documentation. In this study the researchers interviewed informants, the Head of Marketing Communications PT. Bintan Resort Cakrawala, Head of Public Relations of PT. Bintan Resort Cakrawala, and visitors to the Bintan Resort area. The data analysis technique was carried out using the Miles and Huberman analysis model. The research results show that the role of public relations in promoting the Bintan Resorts area during the Covid-19 pandemic is in accordance with the role of marketing public relations, including: namely: growing and developing consumer awareness of products/services during the Covid-19 pandemic, building consumer confidence in the image company or product benefits during the Covid-19 pandemic, encouraging enthusiasm (sales force) during the Covid-19 pandemic by maximizing the use of internal digital media, reducing the cost of promoting commercial advertisements during the Covid-19 pandemic, public relations commitment for the Bintan Resort Area to improving services to consumers during the Covid-19 pandemic, campaigning for the launch of new products, communicating continuously through media public relations about activities and work programs during the Covid-1 pandemic, promoting and maintaining the company's reputation for its goods and services, and always take the initiative to overcome any negative situations that arise g may have appeared during the Covid-19 pandemic. Bintan Resorts adalah kawasan pariwisata andalan Kepulauan Riau yang merasakan dampak ekonomi akibat pandemi Covid-19. Berbagai upaya dilakukan untuk mempertahankan keberlangsungan bisnis kawasan Resort Bintan, salah satunya dengan meningkatkan promosi melalui peran Public Relations. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kehumasan membantu mengiklankan kawasan Resort Bintan selama pandemi Covid-19. Menggunakan kalimat hasil wawancara, pendekatan penelitian ini menggunakan deskriptif kualitatif untuk melihat, mengidentifikasi, dan menjelaskan fungsi kehumasan dalam mempromosikan kawasan Bintan Resort di masa pandemi Covid-19. Metode penelitian menggunakan studi kasus atau kasus tunggal, berupa aktivitas perusahaan PT. Bintan Resort Cakrawala. Subjek penelitian adalah Public Relations PT. Bintan Resort Cakrawala, sedangkan objek penelitian adalah peran public relations dalam mempromosikan kawasan Resort Bintan. Teknik pengumpulan data dengan wawancara, obervasi, dan dokumentasi. Dalam penelitian ini peneliti mewawancarai para informan, yaitu head of marketing communications PT. Bintan Resort Cakrawala, head of public relations PT. Bintan Resort Cakrawala, dan pengunjung kawasan Resort Bintan. Teknik analisis data dilakukan dengan model analisis Miles dan Huberman. Hasil penelitian diketahui bahwa peran public relations dalam mempromosikan kawasan Resort Bintan di masa pandemi Covid-19 sesuai peranan marketing public relations, antara lain adalah menumbuh dan kembangkan kesadaran konsumen terhadap produk/jasa di masa pandemi Covid-19, membangun kepercayaan konsumen terhadap citra perusahaan atau manfaat atas produk di masa pandemi Covid-19, mendorong antusiasme (sales force) di masa pandemi Covid-19 dengan memaksimalkan penggunaan media digital internal, menekan biaya promosi iklan komersial di masa pandemi Covid-19, public relations kawasan Resort Bintan dalam rangka meningkatkan pelayanan kepada konsumen di masa pandemi Covid-19, mengkampanyekan peluncuran produk-produk baru, mengkomunikasikan terus-menerus melalui media public relations tentang aktivitas dan program kerja di masa pandemi Covid-19, mempromosikan dan menjaga reputasi perusahaan untuk barang dan jasanya, dan selalu mengambil inisiatif untuk mengatasi setiap situasi negatif yang mungkin muncul selama pandemi Covid-19.